RANCANG BANGUN ROBOT HUMANOID PENARI GENDING SRIWIJAYA MENGGUNAKAN MODUL EASYVR3 - Rana Zahra; Thamrin Thamrin; Putra Jaya (Universitas Negeri Padang, 2017)
The purpose of this final project to produce humanoid robot that can perform Gending Sriwijaya dance movement by using speech recognition module. There is an asynchronization between the music accompaniment detection movement of humanoid robot on Gending Sriwijaya dance at Kontes Robot Seni Tari Indonesia 2017. Use of speech recognition moduls input system given the solution of the problem.System requirements were divided into hardware and software included robot acuator components suh as 25 servo motors, robot controllers such as CM-530 and Arduino Mega, EasyVR3 speech recognition module, battery. There three software used to complied humanoid robot. EasyVR Commander software for the detection and synchronization of voice input, Roboplus software for making movements on humanoid robot, Arduino IDE software for programming of humanoid robot movement control system. The design of this humanoid robot system is divided into 3 parts, input of the system is Gending Sriwijaya music which is detected by the speech recognition module, the controlling process of the system is Arduino Mega and CM-530, and the output of the system is the movement of humanoid robot which is formed from the combination of rotation Angle servo motor. The result of this final project is successfully working humanoid robot that can perform Gending Sriwijaya dance movement by using speech recognition module EasyVR3. Furthermore, has successfully worked the program of detection and synchronization of voice, program control system movement of humanoid robot in dance Gending Sriwijaya in the form of movement walkready, sembah buka, cubung bawah, cubung atas, silang, transisi berdiri ke duduk (sembah duduk), borobudur, transisi duduk ke berdiri (sembah diri), ukel benang , sembah tutup, dan jalan. Keywords: humanoid robot, speech recognition, Gending Sriwijaya dance